Serial tissue Doppler imaging in the evaluation of bronchopulmonary dysplasia-associated pulmonary hypertension among extremely preterm infants: a prospective observational study - Gopagondanahalli, Krishna Revanna; Abdul Haium, Abdul Alim; Vora, Shrenik Jitendrakumar; Sundararaghavan, Sreekanthan; Ng, Wei Di; Choo, Tze Liang Jonathan; Ang, Wai Lin; Binte Mohamad Taib, Nur Qaiyimah; Wijedasa, Nishanthi Han Ying; Rajadurai, Victor Samuel; Yeo, Kee Thai; Tan, Teng Hong (Frontiers in Pediatrics, 2024)
Objectives To evaluate serial tissue Doppler cardiac imaging (TDI) in the evolution of bronchopulmonary dysplasia-associated pulmonary hypertension (BPD-PH) among extremely preterm infants. Design Prospective observational study. Setting Single-center, tertiary-level neonatal intensive care unit. Patients Infant born <28 weeks gestation. Main outcome measures Utility of TDI in the early diagnosis and prediction of BPD-PH and optimal timing for screening of BPD-PH. Results A total of 79 infants were included. Of them, 17 (23%) had BPD-PH. The mean gestational age was 25.9 ± 1.1 weeks, and mean birth weight was 830 ± 174 g. The BPD-PH group had a high incidence of hemodynamically significant patent ductus arteriosus (83% vs. 56%, p < 0.018), longer oxygen days (96.16 ± 68.09 vs. 59.35 ± 52.1, p < 0.008), and prolonged hospital stay (133.8 ± 45.9 vs. 106.5 ± 37.9 days, p < 0.005). The left ventricular eccentricity index (0.99 ± 0.1 vs. 1.1 ± 0.7, p < 0.01) and the ratio of acceleration time to right ventricular ejection time showed a statistically significant trend from 33 weeks (0.24 ± 0.05 vs. 0.28 ± 0.05, p < 0.05). At 33 weeks, the BPD-PH group showed prolonged isovolumetric contraction time (27.84 ± 5.5 vs. 22.77 ± 4, p < 0.001), prolonged isovolumetric relaxation time (40.3 ± 7.1 vs. 34.9 ± 5.3, p < 0.003), and abnormal myocardial performance index (0.39 ± 0.05 vs. 0.32 ± 0.03, p < 0.001). These differences persisted at 36 weeks after conceptional gestational age. Conclusions TDI parameters are sensitive in the early evolution of BPD-PH. Diagnostic accuracy can be increased by combining the TDI parameters with conventional echocardiographic parameters. BPD-PH can be recognizable as early as 33–34 weeks of gestation.